Experimental and Thermodynamic Investigation on CO2 Absorption in Aqueous MEA Solutions. (13th October 2022) - Zhu, Kai; Yue, Changhai; Wei, Zhenhao; Huang, Jingjing; Hu, Meng; Ji, Yufan; Liu, Hanfei; Zhu, Hao; Guo, Wanxiao; Zhou, Feng; Yao, Chaoqun; Huang, Yiping
Abstract : The vapor-liquid equilibrium (VLE) of CO2 in a reactive solvent is essential for the proper simulation and design of CO2 absorption processes. This work presents a systematic investigation on CO2 absorption in various aqueous monoethanolamine (MEA) solutions. CO2 solubility in MEA was measured at 298, 313, 333, and 353 K with CO2 partial pressure ranging from 34.5 to 78.0 kPa. A modified Kent-Eisenberg model was developed based on the measured solubility data, showing good predictions over the liquid phase speciation for the CO2- H2 O-MEA system. We presented a new analysis based on the first-order difference curve of distribution profiles of the species. Based on the main reactions that occurred, the CO2 absorption process was demonstrated to be divided into four regions with increasing CO2 loading from 0 to 1. Accordingly, kinetic study was proposed to be conducted in the first region, whereas measuring of mass transfer in the first three regions. The findings in this work extend the existing knowledge of CO2 absorption process in terms of speciation and can provide important guidance for further study of the process characteristics using aqueous amine absorbents.